Self-Esteem, Adolescence, and Pedagogy - Itzel Silva-Escorcia; Omar Mejía-Pérez (Revista Electrónica Educare)
Self-esteem in teenagers is a very important matter first for teenagers, second for their educational process, and finally for education itself, as educated individuals are productive for society.  Self-esteem is the element that can significantly increase students’ academic motivation as well as a favorable emotional state to achieve adequate school performance and educational development, as an individual and as a collective subject aiming towards fulfillment.  It is very important that teachers know the self-reference elements that shape and nurture self-esteem in order to work with them as educational processes and thus fortify their holistic pedagogical task.